The Effect of Creating Learning Videos by Teachers with Language Development on Distance Learning in the Pandemic Period at Kindergarten B Ananda Islamic School Jakarta - Femi Indriyatama; Nurlita Sari (Universitas Muhammadiyah Ponorogo, 2022)
COVID-19, which is still hitting Indonesia today, has made learning that was previously a face-to-face system to be changed to distance education. Teachers are required to have the competence to make distance learning media that is fun for students so that the expected learning objectives can be achieved, one of them is by making learning videos. This study aimed at analyzing the use of animated video media in early childhood. This research used a quantitative research approach with a descriptive survey method. The samples were 28 students who received animation video media stimulation from three teachers at the school. This research used Quasi Experiment Method. Hypothesis testing used the previous t-test in the form of prerequisite tests for normality analysis and homogeneity of variance. The study result indicated the value of 0.000 0.05, so there was an average difference between the pretest and posttest learning outcomes, which means that there was an effect of using peer tutor learning strategies in improving learning outcomes.